2022
DOI: 10.1111/mcn.13325
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal involvement in complementary feeding in Kaduna State, Nigeria: The continuum of gender roles in urban and rural settings

Abstract: Household gender roles influence infant and young child feeding behaviours and may contribute to suboptimal complementary feeding practices through inequitable household decision-making, intra-household food allocation and limited paternal support for resources and caregiving. In Igabi local government area of Kaduna State, Nigeria, the Alive & Thrive (A&T) initiative implemented an intervention to improve complementary feeding practices through father engagement. This study describes household gender roles am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Due to the acceptable levels of agreement between mothers’ and fathers’ measurements of fathers’ complementary feeding support (percentage agreement ranged from 52.1% to 89.1%), only mothers’ measurement variables were used in the logistic regression and interaction models. The decision is also further supported by our qualitative findings from the same study ( 56 ), which indicated that the traditional roles of mothers as primary caregivers for children still prevail. Therefore, mothers’ perspectives can be more relevant in reflecting the types of support received.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Due to the acceptable levels of agreement between mothers’ and fathers’ measurements of fathers’ complementary feeding support (percentage agreement ranged from 52.1% to 89.1%), only mothers’ measurement variables were used in the logistic regression and interaction models. The decision is also further supported by our qualitative findings from the same study ( 56 ), which indicated that the traditional roles of mothers as primary caregivers for children still prevail. Therefore, mothers’ perspectives can be more relevant in reflecting the types of support received.…”
Section: Methodssupporting
confidence: 61%
“…Both domains of complementary feeding support had substantial agreement between mothers’ and fathers’ reports, suggesting that most fathers in Kaduna support complementary feeding mainly by providing money for food, with less provision of “caregiving support.” Fathers’ roles as “providers or suppliers” have been documented in several studies as helpful in improving availability of diverse complementary foods ( 8 , 17 , 18 , 65 , 66 ). A previous qualitative article on household gender roles and paternal/maternal involvement in complementary feeding from this same study in Kaduna showed that fathers’ perspectives of their traditional roles as “providers” influence their involvement and support for complementary feeding ( 56 ). The similarities in both the qualitative and quantitative findings suggest that future SBCC interventions in Kaduna could leverage the traditional roles of fathers as “providers” to continue their financial support for complementary feeding so mothers can exercise their autonomy to purchase and feed recommended complementary foods to children.…”
Section: Discussionmentioning
confidence: 94%
“…To streamline the review process according to the WHO practical guide to rapid reviews [43], a single reviewer (DM) conducted quality assessment of the studies. The Critical Appraisal Skills Programme (CASP) ten-question qualitative studies checklist [12] was used to assess the methodological quality of qualitative studies (of which there were seven [14, 1619, 24, 26]), and the 12-question cohort study edition was used for one study [20]. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) 22-item cross-sectional study checklist [13] was used for all studies with a quantitative component, of which there were seven [15, 21–23, 2528].…”
Section: Methodsmentioning
confidence: 99%
“…Several mothers from rural settings described how rural fathers were less helpful in childcare and parenting than those from urban settings [14]. Urban fathers reported more instances of decision-making with mothers to equally divide parenting roles and were more likely to engage in completing household chores and buying nutritious food for not only their children but also their mothers [14]. Fathers' level of education was also important in influencing how they interact with their children, as more educated fathers reported the importance of a balanced diet and nurturing environment for children's early development [19].…”
Section: Urban and Rural Differencesmentioning
confidence: 99%
“…There are several areas future research can focus on. Future research should include mothers, fathers and grandmothers in the same households to better understand family dynamics and how IYCF interventions targeted at different family members affect them(Allotey et al, 2022).Future research should also focus on understanding attitudes, beliefs, social norms and roles of child nutrition influencers to enhance intervention effectiveness. Finally, future research in LMICs should continue to include social norms as a construct for exploration to continue to build the evidence base for social norms and health behaviour in these contexts.…”
mentioning
confidence: 99%